Métodos de acoplamento para problemas com interação térmica entre fluido e sólido - Nabbout, Kaissar (2020)
The analysis of problems of thermal interaction between fluid and solid in a coupled manner represented a major advance for the development of equipment and thermal systems present in the daily lives of people and companies. Many advances have been made since the first works presented in the 1960s, in which analytical solutions to problems with simple geometries emerged. With the advance of the processing capacity of computers and the development of new numerical methods, increasingly accurate solutions to CHT problems (Conjugate Heat Transfer) are achieved, which results in the development of increasingly efficient processes. The main objective of the present work is to study ways to make the thermal coupling between different subdomains and to implement a computational code capable of solving a thermal transfer problem in a conjugated manner. The chosen problem was the flow over a flat plate, which has an analytical solution that will be used to validate the numerical and computational methods used. The results obtained were compared with the analytical model presented by Shah e Jain (2015).